PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS KEARIFAN LOKAL KEPULAUAN RIAU UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA SMP - Putriyani, Anita; Dwinata, Alona; Elvi, Mariyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The aim of this study is to develop a learning video based on the local wisdom of the Riau Islands that is valid, practical, and effective for improving the mathematical literacy skills of junior high school students. This study is a development research using the ADDIE model, which consists of five research stages: analysis, design, development, implementation, and evaluation. The instruments used in this study include validation sheets from media and material experts, response questionnaires from teachers and students, and effectiveness instruments in the form of pretest and posttest to see the improvement in students mathematical literacy skills. This research produced a learning video based on the local wisdom of the Riau Islands that is valid with an average score of , which falls into the very valid category, an average practicality score of which is considered practical and an n-gain of , indicating that the learning video is effective in improving students mathematical literacy skills at the moderate level in a limited trial. Therefore, it can be concluded that the developed learning video meets the criteria for being feasible to use in the learning process.